The impact of hospital support function centralization on patient outcomes: A before-after study - Adrien Le Guillou; Jan Chrusciel; Stephane Sanchez (Elsevier, 2021)
Objectives: This study aimed to evaluate the impact of centralizing hospital support functions such as administration, quality monitoring, procurement, and insurance on patient outcomes in a French regional hospital group. Study design: A before-after study was conducted within a medium-sized hospital in a rural region of France including 87,373 hospital stays between 2013 and 2017. Methods: The intervention tested was the centralization of support functions: administration, quality monitoring, procurement, and insurance. The outcomes analyzed were patient mortality, 30 day readmissions and average length of stay. Results: The odds ratio (OR) for patient mortality after centralization was 0.99 (95%CI, 0.92 to 1.06), and 0.94 (95%CI, 0.90 to 0.96) for readmissions. The multiplicative factor for average length of stay was 0.93 (95%CI 0.92-0.94). Conclusions: There was an increase in measured quality of care after the intervention. This study highlights the complexity of assessing the impact of hospital-level centralization on quality-of-care indicators.